Surveillance and genetic diversity analysis of avian astrovirus in China - Fuyou Zhang; Yang Li; Wenming Jiang; Xiaohui Yu; Qingye Zhuang; Suchun Wang; Liping Yuan; Kaicheng Wang; Shuhong Sun; Hualei Liu (PLoS ONE, 2022)
Avian astroviruses (AAstVs) have caused major problem for poultry breeding industries in China in recent years, and the goose gout caused by goose astrovirus has produced particularly great economic losses. To better understand the prevalence and genetic diversity of AAstVs in China, 1210 poultry samples collected from eight provinces were tested with reverse transcription-polymerase chain reaction (RT-PCR) to detect AAstV infections in different poultry populations. Then, Open reading frames 2 (ORF2) was amplified by specific primers, and the genetic evolution was analyzed. Our surveillance data demonstrate the diversity of AAstVs in China insofar as we detected 17 AAstVs, including seven chicken astroviruses (CAstVs), five avian nephritis viruses (ANVs), two goose astroviruses (GoAstVs), two duck astrovirus (DAstVs), and one new AAstV belonging to Avastrovirus Group 3. The positive rate of AAstV infection was 1.40%. Host analysis showed that CAstVs and ANVs were isolated from chickens, DAstVs and GoAstVs were isolated from ducks. Host-species-specific AAstVs infections were also identified in numerous samples collected at each stage of production. This study provides further evidence to better understand the epidemiology of AAstVs in different species of poultry in China.